Transformasi Peran Guru Sejarah di Era Digital dalam Perspektif Society 5.0 - Tama Maysuri; Reihana Kapitanhitu; Siti Mussa’adah; Susi Harnisa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The transformation of education in the digital age demands fundamental changes to the role of history teachers to align with the Society 5.0 paradigm, which positions technology as a means of enhancing the quality of learning. This study aims to analyse the transformation of the history teacher’s role, the challenges faced, and adaptation strategies in 21st-century learning. This study employs a qualitative method with a descriptive approach through case studies. Data collection techniques include in-depth interviews, observation, and document analysis, whilst data analysis utilises an interactive analysis model comprising data reduction, data presentation, and drawing conclusions. The research findings indicate that history teachers no longer act merely as conveyors of subject matter, but have evolved into learning facilitators, curators of digital historical sources, innovators of learning media, and mentors in digital literacy and character development for students. The use of technologies such as Learning Management Systems, interactive multimedia, digital archives, virtual tours of historical sites, and artificial intelligence is capable of increasing student participation and strengthening a more critical and contextual understanding of history. However, this transformation still faces obstacles in the form of limited digital competence among teachers, infrastructure gaps, and a lack of continuous training. The limitation of this study lies in the research focus, which is still limited to a certain context and uses a qualitative approach. Future research is recommended to expand the scope of the study and combine a quantitative approach in order to obtain more comprehensive results